STRATEGIC PLANNING OF MACHINE-BUILDING ENTERPRISE MANAGEMENT SYSTEM ON THE BASIS OF ACTIVATION OF FOREIGN ECONOMIC ACTIVITY - SAVITSKYI Аndrii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The paper deals with the issue of strategic planning of management system of machine-building enterprise based on activation of its foreign economic activity (FEA) and export positions. Certain aspects of development of machine-building industry at the current stage of cyclical transformations of Ukraine’s economy under conditions of military state and enhanced integration into European Union have been presented. There were analyzed current tendencies of machine-building enterprises’ performance as one of the core fields of Ukraine’s economy. Using the example of separate business entity, the expediency of thoughtful strategic planning of enterprise’s management system has been emphasized, the place of export activity has been characterized. In order to improve management system, the elements that shape development of machine-building enterprise and aimed to stimulate export have been grouped. The essence of internal and external elements of management was defined. The steps of strategic planning and solving key problems on operational level of an enterprise were proposed. Problematic issues that arise as the result of Ukraine’s economic transition stages and its influence on enterprise’s strategic planning have been interpreted. The importance of enterprise’s unit that connected to the questions of FEA activation from the side of costs for management functions implementation has been characterized, following changes to the organizational structure have been proposed. The main actions that deals with cost management, profitability and competitiveness have been grouped, the instruments of economic analysis, budgeting and foreign trade marketing were emphasized. As the results, it was built the structure of algorithm for making an export-oriented development strategy in the strategic planning of enterprise’s management system. It was proposed subsystem of market current situation evaluation, subsystem of defining and adaptation of export-oriented development strategy conception, subsystem of export potential efficiency and subsystem of export-oriented development strategy alternatives.